Poetics of Title in Ivan Bunin’s Short Story “The Emerald” - E. V. Ushakova (Научный диалог, 2024)
This article explores the poetics of the title in Ivan Bunin’s short story “The Emerald” from the collection “Dark Avenues,” which represents a small scene or prose miniature with a weakened plot. The novelty of the research lies in the analysis of the title of this work and its connection not only to the story “The Emerald” but also to Bunin’s overall body of work. The role of the expositional landscape and conflict development is revealed within the thematic context of the narrative. Key moments of the collision dynamics in the story, based on dialogue and contrast principles, are identified. Parallels between the stories “The Emerald” and "Pure Monday" are drawn, noting similarities in character portrayal: the heroines strive for the divine, are sensitive to celestial beauty, which is not understood by their lovers as bearers of a more rational and earthly mindset. The peculiarities of the poetics of the title, its connections to biblical texts, and comparisons with the writer’s poetic and prose works are explored. The author concludes that the image of an emerald (or an emerald) in Bunin’s works correlates with the divine and sublime world, symbolizing the spiritual aspirations of the heroine in the story “The Emerald” and present in other works by Bunin, embodying a longing for spiritual existence.